Additional Evaluation of the Point-of-Contact Circulating Cathodic Antigen Assay for Schistosoma mansoni Infection - Mwinzi, Pauline N. M.; Kittur, Nupur; Ochola, Elizabeth; Cooper, Philip J.; Campbell, Carl H.; King, Charles H.; Colley, Daniel G. (Frontiers in Public Health, 2015)
Studies of the urine-based point-of-contact Cathodic Circulating Antigen test (POC-CCA) in S. mansoni-endemic settings in Africa indicate it has good sensitivity in detecting infections, but in areas of low prevalence, the POC-CCA can be positive for persons who are egg-negative by Kato-Katz stool assays. We examined the POC-CCA assay for: a) batch- to-batch stability; b) intra-reader and inter-reader variability; c) day-to-day variability compared to Kato-Katz stool assays, and d) to see if praziquantel (PZQ) treatment converted Kato-Katz-negative/POC-CCA positive individuals to POC-CCA negativity. We found essentially no batch-to-batch variation, negligible intra-reader variability (2%) and substantial agreement for inter-reader reliability. Some day-to-day variation was observed over 5 days of urine collection, but less than the variation in Kato-Katz stool assays over 3 days. To evaluate the effect of treatment on Kato-Katz(-) /POC-CCA(+) children, 149 children in an area of 10-15% prevalence who were Kato-Katz(-) based on 3 stool samples but POC-CCA(+) were enrolled. Seven days after treatment (PZQ 40mg/kg) samples were again collected and tested. Almost half (47%) POC-CCA positive children turned negative. Those still POC-CCA positive received a second treatment, and 34% of them turned POC-CCA negative upon this second treatment. Most who remained POC-CCA positive shifted each time to a "lesser" POC-CCA "level of positivity”. The data suggest that most Kato-Katz-negative/POC-CCA positive individuals harbor low intensity infections, and each treatment kills all or some of their adult worms. The data also suggest that when evaluated by a more sensitive assay, the effective cure rates for PZQ are significantly less than those inferred from fecal testing. These findings have public health significance for the mapping and monitoring of Schistosoma infections and in planning the transition from schistosomiasis morbidity control to elimination of transmission.